La Guerra Civil y el franquismo en Zumarraga = : Gerra Zibila Eta Frankismoa Zumarragan / Antonio Prada Santamaría, Maialen Aranguren Alonso, Ana Peą Fernández - Aranguren Alonso, MaialenPeą Fernández, Ana; Prada Santamaría, Antonio
Incluye referencias bibliográficas